RAGAM ALTERNATIF MEDIA PEMBELAJARAN PAI BERBASIS PSIKOMOTORIK SELAMA MASA PANDEMI DI MA PERSIAPAN NEGERI 4 MEDAN - Abdul Muthalib; Aisyah Aisyah; Endang Sukari; Rafika Aulia (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2020)
The development of the Covid-19 outbreak has indeed had a major impact on all sides of human life, including in the world of education. The world of education seems to make the house an educational institution that can replace formal educational institutions. Learning using the internet network or so-called brave learning (online). Brave learning may be new to some teachers, but maybe some already consider it familiar. The purpose of this study was to find out about the Variety of Alternative Psychomotor-based PAI Learning Media During Covid-19 at MA Preparation 4 Medan.The results obtained from this research are learning that can be done in any condition, but of course the results will not be optimal learning that is done face-to-face in the classroom. To optimize it, of course many are done by teachers. Especially in the PAI subject, several innovations have been made to optimize learning outcomes, namely: 1) Innovations such as presenting learning with multimedia, 2) Online-based discussions and assignments. Teaching also has obstacles in its application, especially in the MA preparatory 4-field country, some of these obstacles: 1) Signal interference that cannot be avoided. 2) Lack of parental and teacher cooperation in managing courageous learning. 3) Limited costs make students reluctant to take bold lessons.